La Passion selon Saint Jean de Jean Sébastien Bach - Delhaye, Louis (Antwerp Flandria, 1908)
This book discusses the Passion of Jesus Christ according to the Gospel of John, but it focuses primarily on Bach's music. Delhaye explores the theological and spiritual significance of Bach's music, as well as its historical and musical importance. He also examines the different versions of Bach's St John Passion, focusing on the differences between the versions and explaining why some are considered superior to others. Finally, Delhaye examines how Bach's St John Passion has been interpreted and performed over the years, focusing on historical and contemporary performances.
Keywords: Bach, Johann Sebastian -- 1685-1750; Passion; Performance; Music history; Religion